Meaning Construction of Celebrities Popularity as a Political Commodity in Millenial Generation - Ferra Martian; Alexandria Cempaka Harum (West Science Social and Humanities Studies, 2024)
This research uses a qualitative research and constructivist paradigm. Data collection technique using in-depth interviews with representatives of millennial political activists in Indonesia from PSI (Partai Solidaritas Indonesia). Research result shows meaning of politics according to PSI millennial generation politicians includes: life, self-awareness, basic obligations, benefiting people many, power, interests, collective work, policies binding, bringing change, bringing prosperity. The political meaning of these components are the internalization of those whoever been in apolitical thinking. There is further scrutiny regarding the progress of Indonesian celebrity politicians, who are considered to only be based on the aspect of being close to millennials but not touching conscience, people's beliefs and ethical principles. The involvement of millennial politicians is in practical politics including a form of self-actualization by participating fighting for anti-corruption and anti-intolerance, with enthusiasm Bhinneka Tunggal Ika includes: transparency, honesty, never giving up, breaking old standards, and competing skillfully so that you can showing pride in politics. Millennial politicians tried to attend with a new political spirit and style as a breakthrough and antithesis from baby boomer. On the other hand, society has not been fully touched by political literacy so it does not attach much importance to the vision and mission and background of politicians.